2017
DOI: 10.3390/brainsci7120166
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Brain Tumor Surgery for Glioblastoma in Adults

Abstract: Glioblastoma (GBM) is the most common primary intracranial neoplasia, and is characterized by its extremely poor prognosis. Despite maximum surgery, chemotherapy, and radiation, the histological heterogeneity of GBM makes total eradication impossible, due to residual cancer cells invading the parenchyma, which is not otherwise seen in radiographic images. Even with gross total resection, the heterogeneity and the dormant nature of brain tumor initiating cells allow for therapeutic evasion, contributing to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
161
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(183 citation statements)
references
References 83 publications
1
161
0
1
Order By: Relevance
“…Whilst the bulk of the tumour can often be resected, GBM almost always re-occur due to the rapid proliferation of infiltrative residual tumour cells. New growth typically originates from the walls of the surgical cavity or parenchyma within <2 cm of the tumour margin [10]. This is due to small patches of GBM, the "scout" cells, which infiltrate the area adjacent to the tumour.…”
Section: The Problemmentioning
confidence: 99%
“…Whilst the bulk of the tumour can often be resected, GBM almost always re-occur due to the rapid proliferation of infiltrative residual tumour cells. New growth typically originates from the walls of the surgical cavity or parenchyma within <2 cm of the tumour margin [10]. This is due to small patches of GBM, the "scout" cells, which infiltrate the area adjacent to the tumour.…”
Section: The Problemmentioning
confidence: 99%
“…Glioblastoma multiforme remains the most aggressive and lethal form of astrocytoma, with a median patient survival time of only 12 months, and accounts for the majority of primary malignant brain tumors among adults. 1,2 With the advancement of medical technology, the treatment of glioma has progressed, with surgery, radiotherapy, and chemotherapy being the conventional means of treatment, but still results in a high recurrence rate. 3,4 Evidence has shown that the most prevalent reason for cancer recurrence is the uncontrollable growth and high invasiveness of cancer cells, with epithelial-to-mesenchymal transition (EMT) being one of the causes of this recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we showed that glioblastoma multiform cell lines (GBM) expressed Tau protein. GBM grade IV tumors account for 52 to 75% of diagnosed gliomas with a patients' median survival of only 15 months (Figarella-branger et al, 2013;Lara-Velazquez et al, 2017;Weller, 2018). The highly invasive phenotype of GBM tumors renders their complete surgical resection difficult and limits the efficacy of radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%